2010
DOI: 10.1108/20425961201000020
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating entrepreneurship in Africa

Abstract: Entrepreneurship is lauded as an engine of economic development and job creation, with SMEs often creating most of the new jobs in many countries. This paper identifies some important factors that contribute to the start-up and success of new business ventures in Africa, emphasizing that while personality factors such individual drive and competency and availability of resources are important for the successful launch of a new business venture, effective government policy is also critical in promoting successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…Entrepreneurs operating in developing countries are constrained by scarcity; for example lacking adequate start-up capital, stiff competition, lack of employees with the right skills, difficulty in finding adequate facilities to start their business (Sriram and Mersha, 2010). A 'refusal to be constrained by limitations' can be taken as the de facto starting point in both cases; both innovator-entrepreneurs were aware of the limited resources, but were not willing to be discouraged under such conditions.…”
Section: Identifying Opportunities For Innovating: Recognizing Needs supporting
confidence: 57%
See 1 more Smart Citation
“…Entrepreneurs operating in developing countries are constrained by scarcity; for example lacking adequate start-up capital, stiff competition, lack of employees with the right skills, difficulty in finding adequate facilities to start their business (Sriram and Mersha, 2010). A 'refusal to be constrained by limitations' can be taken as the de facto starting point in both cases; both innovator-entrepreneurs were aware of the limited resources, but were not willing to be discouraged under such conditions.…”
Section: Identifying Opportunities For Innovating: Recognizing Needs supporting
confidence: 57%
“…As the example of the wind-turbine illustrates, here the innovator held intimate knowledge of both local needs and the technological potential of wind energy. Knowledge of local needs combined with certain personality characteristics, such as passion, energy, persistence and determination, may be important drivers in an uncertain environment, as is the case in many African countries (Sriram and Mersha, 2010).…”
Section: Bricolage In the Context Of The Innovation And Entrepreneursmentioning
confidence: 90%
“…Developing countries such as South Africa are starting to adopt a culture of establishing more SMMEs in order to reduce the growing unemployment rate in the country (Kingdon & Knight, 2007). SMMEs have an important role to play in transitioning and developing countries such as South Africa (Sriram & Mersha, 2010) and its development and promotion have been one of the key policy focus areas in South Africa since 1995 (Rogerson, 2011). The SMME sector has the potential to reduce poverty and help to create jobs (Amra et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since SMMEs are seen as vital to the economy's prosperity, without the development of these institutions the economy can risk being stagnant and even show no economic growth (Snyman et al, 2014). SMMEs have an important role to play in transitioning and developing countries such as South Africa (Sriram & Mersha, 2010). SMME development and promotion has been one of the key policy focus areas in South Africa since 1995 (Rogerson, 2011).…”
Section: Survivalist Enterprisementioning
confidence: 99%
“…One of their key recommendations was for government to make available the enabling environment for private sector led investment through the delivery of suitable infrastructural amenities. Sriram and Mersha [28] discussed the factors that contribute to success of new business venture in Africa especially the start-up. They reported that effective government policy is very crucial in encouraging successful business enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%